Health Effects of Calcium: Evidence From Mendelian Randomization Studies. (31st August 2021) - Chen, Yiheng; Forgetta, Vincenzo; Richards, J. Brent; Zhou, Sirui
ABSTRACT: Calcium is widely used in conjunction with vitamin D to prevent osteoporosis. The use of calcium supplementation is also promoted for its potential benefits in lowering the risk for metabolic syndromes and cancers. However, the causal link between calcium and various health outcomes remains unclear. This review focuses on the evidence from 24 Mendelian randomization (MR) studies that were designed to minimize bias from confounding and reverse causation. These MR studies evaluated the effect of lifelong genetically higher serum calcium levels on various health outcomes. Overall, available MR studies found no conclusive effects of serum calcium levels on bone mineral density and fracture, ischemic stroke and heart failure, cancers, type 2 diabetes, Parkinson disease, or offspring birth weight. However, a higher serum calcium concentration was reported to have estimated causal effects on increased risks for coronary artery disease (especially myocardial infarction), migraine, renal colic, allergy/adverse effect of penicillin, and reduced risks for osteoarthrosis and osteoarthritis. In conclusion, supplementation of calcium in individuals from the general population is not predicted to influence the risk of most investigated diseases to date. Moreover, long‐term high serum calcium concentrations may result in adverse health outcomes. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.